Factors influencing medical professional adoption of electronic health record in Jordan Hospital - Al Azzam, Malik Bader Hasan (2017)
Electronic health records (EHRs) have proven to improve hospital quality, reduces health costs and medical errors. Currently, EHRs adoption is not completed in Jordan hospitals, and limited research has been done in Jordan government hospitals. The aim of this study is to explore the factors that influence medical professional adoption of EHRs in Jordan Hospital. The problem statement of this study is the low acceptance level of EHRs in Jordan hospitals. A conceptual model, adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT2) model, is built to relate the Individual Context and Trust Factor on the Behavioural Intention to adopt EHRs in Jordan hospitals. Self-administered questionnaires are used to gather the data from healthcare professionals in two major government hospitals that have used EHRs. The results indicated that the effects of Individual Context, Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, Habit, Trust Factors, Trust Information and Trust System on the Behavioural Intention, to use EHRs are significant and positive. The results also indicated that Individual Context is the most significant predictor of the Behavioural Intention to use EHRs. Trust Factors is found as the second most significant predictor. Finally, from the results of moderation analysis, it is found that Age positively moderates the effects of Social Influence, Trust Information and Trust System on Behavioural Intention to use EHRs. However, the effect of Effort Expectancy on the Behavioural Intention to use EHRs is negatively moderated by the Age. The finding of this work has contributed to the growth and enhancement of the theoretical knowledge of UTAUT2 in the medical informatics field. This study has extended the current model and extension of the UTAUT2 model by including Trust Information and Trust System. Therefore, the findings can aid decision makers in formulating EHRs adoption strategies in Jordan hospitals medical informatics.